Vertragliche Rechtsfolge der «Verwendung missbräuchlicher Geschäftsbedingungen» - Pfeiffer, Reto (sui generis Verlag, 2021)
This dissertation seeks an answer to the question of what the "contractual legal consequence" - i.e., the effect on the contract - is when parties conclude a contract that contains general terms and conditions that are unlawful - i.e., "unfair" (according to the subject heading of Art. 8 UCA) - under Art. 8 UCA. The contractual legal consequence, in turn, has several aspects, and the paper deals with two of them. In a first, shorter part, it is examined whether contracts concluded using unfair terms and conditions are voidable only or whether they are void "ex officio," "eo ipso," "ex lege." In a second part, it is examined whether between the parties of such a contract what they just could have permissibly agreed (i.e., a "geltungserhaltende Reduktion" of the impermissible agreement takes place) applies, or whether the legal relationship between the parties is worse for the "AGB user" than what the parties just could have permissibly agreed.